New data on Callovian (Middle Jurassic) belemnites and palynomorphs from the Northern Caucasus, southwest Russia - Dzyuba, Oksana S.; Goryacheva, Anna A.; Ruban, Dmitry A.; Gnezdilova, Victoria V.; Zayats, Pavel P. (Geologos, 2016)
Palaeontological data on the Caucasus are highly important for large-scale stratigraphical and palaeobiogeographical assessment of the northern Tethyan margin, but this information is often scarce and not available in English. Field studies in the Northern Caucasus have now permitted to amass some new data. Two belemnite species are described from the stratotype section of the Kamennomostskaja Formation (Callovian, Middle Jurassic) near the town of Kamennomostskij in Adygeja (Northern Caucasus). These are Belemnopsis subhastata (von Zieten, 1831) and Rhopaloteuthis ominosa Gustomesov, 1968. The latter is a rare species, and the present find allows new insights into its taxonomy. A palyno-logical analysis of the belemnite-bearing sample was carried out, and a diverse assemblage of dinocysts, acritarchs and prasinophytes, plus pollen and spores recognised. The most abundant palynomorphs are Micrhystridium and Classopollis. Data on belemnites coupled with those on palynomorphs indicate the early Callovian age of the sample level. This interpretation differs slightly from previous conclusions based on ammonites and dinocysts. If this age is correct, the degree of condensation of Callovian deposits in the section studied was lesser than previously assumed.